Aktualisasi Prinsip Negara Hukum Pasca Putusan Mahkamah Konstitusi Nomor 60/PUU-XXII/2024 - Muhammad Anwar Soleh (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The problem of organizing regional elections has been apparent since the nomination stage where there are obstacles for each regional head, namely the regional head nomination threshold. The nomination threshold directly eliminates the constitutional and political rights of every citizen to actively participate in the regional head election process. This study uses normative legal research, namely preliminary research activities before delving further into in-concrito research. The research approach uses a statute approach and a case approach through the Constitutional Court decision Number 60/PUU-XXII/2024. The statute approach is carried out to trace the laws and regulations related to the research theme being studied. The results of the discussion obtained, namely the Constitutional Court's decision regarding changes to the regional head nomination threshold, are a good sign for the future of democracy. The people have almost lost trust recently in the democratization process with the behavior of political party elites in nominating regional heads who tend to lead to cartel politics. Of course, this decision needs to be welcomed and the Constitutional Court deserves appreciation because this decision was issued amidst the strengthening of cartel politics in the nomination of regional heads. The Constitutional Court's decision has changed the basis of the requirements that must be met by political parties or coalitions of political parties in registering regional head candidate pairs from obtaining seats or accumulation of valid voters to only obtaining valid voters by determining the percentage.